Pharmacoeconomic analysis of long term use of darbepoetin-α in treating chronic nephropathy-induced anemia in dialysed patients - Giotta, Nicola; Biamino, Ercole; Eandi, Mario (Farmeconomia. Health economics and therapeutic pathways, 2007)
The main aim of this retrospective study was to perform a pharmacoeconomic analysis of long term use of darbepoetin-α (DARB) after switch from erythropoietin-ß (EPO-ß) in treating chronic nephropathy-induced anemia in dialysed patients. Secondary objective was the assessment of the actual EPO-ß-to-DARB dose conversion factor. We extracted data of 78 patients who have been treated with EPO-ß for at least 6 months and then switched to DARB from the database of the dialysis center of the Asti (Piedmont, Italy) hospital. From these, we selected 47 patients (23 males and 24 females) who completed a 120-weeks follow-up treatment with DARB. All patients were treated with a dose adjustment schedule to keep haemoglobin levels in the range 11-12g/dl. Pre-switch EPO-ß administration was thrice a week, while DARB was administered once a week, both via intravenous. Initial DARB dose has been calculated on the basis of the theoretical 200:1 conversion factor. Actual cumulative EPO and DARB consumption was recorded for all patients. Drug costs were valued according to purchasing prices for the Italian National Health System (October 2006). In the 24 pre-switch weeks the average cost (±SD) per patient for EPO-ß was € 2,309.86 (±1,434.78). In the 120 weeks of follow-up the average cost (±SD) per patient for DARB/24 weeks ranged from a minimum of € 1,487.09 (±1,125.51) to a maximum of € 2,125.73 (±1,546.85).  The switch of 47 patients to DARB produced an overall net saving for the dialysis centre estimated in 119,540.72 Euro/120 weeks, under the hypothesis that EPO-ß semester costs remain constant: the conversion from EPO-ß to DARB has the potential to maintain long term good haemoglobin control and induces significant savings for the National Health System. However the dosage should be adjusted on an individual basis in order to avoid excessive fluctuation of Hb concentrations. The actual conversion factor resulted on average higher than theoretical factor settling to 240-280:1.